Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Hi asked the following question yesterday: Obtaining the sum of a series

Given the answers to that question by wj32, I am now trying to solve the following problem:

Consider the series
$$\sum_{n=1}^{\infty}\frac{n}{n^4+n^2+1}$$ Use partial fractions to write the general term $$u_n=\frac{n}{n^4+n^2+1}$$
as a difference of two simpler terms

My attempt at a Solution:
The partial fractions are $$\begin{align} \frac{n}{n^4+n^2+1}&=\frac{n+n-n}{n^4+n^2+1}\\ &=\frac{n+n}{n^4+n^2+1}-\frac{n}{n^4+n^2+1}\\ &=\frac{2}{n^3+n+\frac{1}{n}}-\frac{2}{2(n^3+n+\frac{1}{n})} \end{align}$$ Then $$\begin{align} S_n&=\left[\sum_{n=1}^k\frac{2}{n^3+n+\frac{1}{n}}-\sum_{n=1}^k\frac{2}{2(n^3+n+\frac{1}{n})}\right]\\ &=\left[\left(\frac{2}{3}+\frac{4}{21}+\frac{6}{91}+...+\frac{2}{n^3+n+\frac{1}{n}}\right)-\left(\frac{1}{3}+\frac{2}{21}+\frac{3}{91}+...+\frac{2}{2(n^3+n+\frac{1}{n})}\right)\right] \end{align}$$

Here the terms in the left do not cancel the terms in the right?

I'm guessing I need simpler/different partial fractions up at the top?

share|cite|improve this question
up vote 6 down vote accepted

First note that we have a nice factorization of $n^4 + n^2 + 1$. $$n^4 + n^2 + 1 =(n^2+n+1)(n^2-n+1)$$ Hence, $n = \dfrac{(n^2+n+1) - (n^2-n+1)}2$. This gives us $$u_n = \dfrac{(n^2+n+1) - (n^2-n+1)}{2(n^2+n+1)(n^2-n+1)} = \dfrac12 \left(\dfrac1{n^2-n+1} - \dfrac1{n^2+n+1}\right) = \dfrac12 \left(\dfrac1{(n-1)n+1} - \dfrac1{n(n+1)+1}\right)$$ Now telescopic summation should do the job for you Hence, \begin{align} S_N = \sum_{n=1}^{N} u_n & = \dfrac12 \sum_{n=1}^N\left(\dfrac1{(n-1)n+1} - \dfrac1{n(n+1)+1}\right) \end{align} \begin{align} 2S_N & = \sum_{n=1}^N\left(\dfrac1{(n-1)n+1} - \dfrac1{n(n+1)+1}\right)\\ & = \left(1 - \dfrac13 \right) + \left(\dfrac13 - \dfrac17 \right) + \left(\dfrac17 - \dfrac1{13} \right) + \cdots\\ & + \left(\dfrac1{(n-2)(n-1)+1} - \dfrac1{(n-1)n+1}\right) + \left(\dfrac1{(n-1)n+1} - \dfrac1{n(n+1)+1}\right)\\ & = 1 - \dfrac1{n(n+1)+1} \end{align}

share|cite|improve this answer
How do you get $\frac{(n^2+n+1)−(n^2−n+1)}{2(n^2+n+1)(n^2−n+1)}=\frac{1}{2}\left(\frac{1}{n^2−n‌​+1}−\frac{1}{n^2+n+1}\right)$? I don't understand how you break the terms apart to get to the right-hand side of the equals. – Gineer Nov 5 '12 at 6:04
@Gineer $$\dfrac{(n^2+n+1)-(n^2-n+1)}{(n^2+n+1)(n^2-n+1)} = \dfrac{(n^2+n+1)}{(n^2+n+1)(n^2-n+1)}- \dfrac{(n^2-n+1)}{(n^2+n+1)(n^2-n+1)} = \dfrac1{(n^2-n+1)}- \dfrac1{(n^2+n+1)}$$ – user17762 Nov 5 '12 at 6:16

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.